2018
DOI: 10.1101/439935
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A cellular anatomy of the normal adult human prostate and prostatic urethra

Abstract: A cellular anatomy of normal human organs is essential for solving the cellular origins of disease. We report the first comprehensive cellular atlas of the young adult human prostate and prostatic urethra using an iterative process of single cell RNA sequencing and flow cytometry on ~98,000 cells taken from different anatomical regions. Two previously unrecognized epithelial cell types were identified by KRT13 and SCGB1A1 expression and found to be highly similar to hillock and club cells of the proximal lung.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
171
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(187 citation statements)
references
References 62 publications
(92 reference statements)
16
171
0
Order By: Relevance
“…Quantitation of the staining intensity confirmed the significant difference in SULT2B1b between the luminal and basal layer with the luminal layer expressing about 3 to 4 fold higher SULT2B1b than the basal layer (Figure B). Consistent with our findings, an analysis of bulk sequencing from CD26 + luminal epithelia and CD271 + basal epithelia showed a significant enrichment of SULT2B1 in luminal epithelia …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Quantitation of the staining intensity confirmed the significant difference in SULT2B1b between the luminal and basal layer with the luminal layer expressing about 3 to 4 fold higher SULT2B1b than the basal layer (Figure B). Consistent with our findings, an analysis of bulk sequencing from CD26 + luminal epithelia and CD271 + basal epithelia showed a significant enrichment of SULT2B1 in luminal epithelia …”
Section: Resultssupporting
confidence: 91%
“…Luminal and basal epithelial cell populations each express a distinct set of markers, recently delineated by single-cell RNA sequencing. 10 For identification in situ, luminal epithelial cells have historically been identified by cytokeratin 8/18 and PSA (prostate-specific antigen) expression, whereas basal cells express cytokeratin 5/14 and p63. 11 Benign prostate hyperplasia (BPH) is predominantly due to the expansion of the luminal epithelial cells (glandular hyperplasia) with 8% to 10% of BPH cases due to the hyperplasia of the basal layer (basal hyperplasia).…”
Section: Sult2b1bmentioning
confidence: 99%
See 1 more Smart Citation
“…One subgroup (BPH-A) was enriched in stromal signatures 38 ( Figures 3B and S4), again in the validation cohort as well ( Figure 3D and S5). Integrating the stromal cell signatures from single cell RNA-seq on normal prostate tissue 39 further confirmed the stromal enrichment in BPH-A subgroup ( Figure S7). Of note, there was no clear enrichment of stromal cell content visible on histopathology analysis of these samples, suggesting that molecular characterization provided independent information ( Figure S8).…”
Section: Resultsmentioning
confidence: 58%
“…For luminal markers such as KRT8, KRT18, and KRT19, they were expressed in some of the tumor cells ( Figure S4). As there has been suggestion that those markers may be expressed in some intermediate states between luminal and basal cells, 39 to further confirm those tumor cells were of basal origin, we checked other luminal markers, AR, KLK3, and CD26 (DPP4), 19,40 and neither was expressed in the tumor Figure S4). Based on the above observations we concluded that those tumor cells are of basal origin instead of luminal origin, we also verified the expression of basal marker CK14 by immunohistochemistry.…”
Section: Single-cell Rna-seq Reveals the Transcriptomic Features Ofmentioning
confidence: 99%